Reclaiming Cognitive Skills in Electrical Technology: Addressing AI Dependence in South African Technical Schools - Dayi Nzaliseko; Mtshali Thokozani Isaac (Studies in Learning and Teaching, 2026)
This study investigated the growing dependence on artificial intelligence (AI) tools among learners studying electrical technology in South African technical schools and its influence on cognitive and critical thinking skills. The purpose of this study was to examine how excessive dependence on AI affects learners’ problem-solving skills and practical competence, which are important for meeting the demands of the Electrical Technology curriculum and the broader technical industry in South Africa. A quantitative research approach was adopted using a descriptive survey design. Simple random sampling was used to select 120 electrical technology learners from four technical high schools across Gauteng Province, South Africa. The data were collected using structured questionnaires and online surveys focusing on learners’ use of AI, engagement in problem-solving, and performance in Electrical Technology Practical Assessment Tasks (PATs). Furthermore, this data was analyzed using descriptive and inferential statistics. Findings revealed that the majority of learners mostly relied on AI to complete written tasks and PATs, resulting in reduced critical thinking, limited conceptual understanding of electrical concepts, and poor practical performance. The study recommends the integration of digital ethics, guided AI use, and cognitive-based teaching strategies to foster independent reasoning and ensure learners acquire practical skills aligned with industry expectations.